The Rocky Horror picture show [videorecording (Blu-Ray)] - O'Brien, Richard, 1942- (Twentieth Century Fox, 2020)
A screamingly funny, sinfully twisted salute to sci-fi, horror, B-movies and rock music, all rolled into one deliciously decadent morsel. And now there's even more to make watchers shiver with anticipation: two additional musical numbers, Once In A While; and Superheroes; never seen theatrically or available on video! Join Dr. Frank-N-Furter, Brad Majors, Janet Weiss and Eddie: Ex Delivery Boy in the most popular cult classic of all time.